The Effectiveness and Adverse Events of Amitriptyline and Aripiprazole in Very Elderly Patients With BMS - Watanabe, Motoko; Takao, Chihiro; Liu, Zhenyan; Nayanar, Gayatri; Suga, Takayuki; Hong, Chaoli; Tu, Trang Thi Huyen; Yoshikawa, Tatsuya; Takenoshita, Miho; Motomura, Haruhiko; Nagamine, Takahiko; Toyofuku, Akira (Frontiers in Pain Research, 2022)
Burning mouth syndrome (BMS) is defined by chronic oral burning sensations without any corresponding abnormalities. Besides amitriptyline, aripiprazole has been reported as a possible medication to manage BMS. However, especially for elderly patients, the adverse events of these medications would be a problem. The aim of the present study was to investigate the differences in the effectiveness and adverse events of amitriptyline and aripiprazole in very elderly patients with BMS. This is a retrospective comparative study of 80 years old and older patients with BMS who were initially treated with amitriptyline or aripiprazole and who were new outpatients of our department from April 2017 to March 2020. All clinical data, including sex, age, comorbid physical diseases, comorbid psychiatric disorders, the prescribed doses (initial, maximum, and effective dose), prognosis, and adverse events, were collected from their medical charts. Each medication was selected considering their medical history. Amitriptyline was prescribed in 13 patients (11 women, 82.3 ± 2.1 years old) and aripiprazole was prescribed in 27 patients (26 women, 84.2 ± 3.8 years old). There were no significant between-group differences in sex, age, duration of illness, pain intensity, salivation, and psychiatric comorbidity at the first examination. Amitriptyline clinically improved more patients (7 patients, 53.8%) with the effective dose of 10 (7.5, 15.0) mg than aripiprazole (11 patients, 40.7%) of which the effective dose was 1.0 (0.5, 1.5) mg, although there were no significant between-group differences. The adverse events of amitriptyline were found in 9 patients (69.2%) and most patients had constipation (46.2%). For aripiprazole, 7 patients (25.9%) showed adverse events, most of them reported sleep disorder (11.1%). Amitriptyline had significantly longer duration taking medication (p = 0.021) and lower discontinuation (p = 0.043) despite of higher occurrence rate of adverse events (p = 0.015) compared to aripiprazole. These results suggest that both psychopharmacotherapies with a low dose of amitriptyline and aripiprazole are effective for the very elderly patients with BMS. Furthermore, aripiprazole may have some advantages in the adverse events compared to amitriptyline; however, the low dose amitriptyline monotherapy may have more benefit in the effectiveness and tolerability over prudent collaboration with primary physicians.